Healthcare-associated infections and drug resistance in immunocompromised children with cancer in a low income country - Rahat Ul Ain, Mahwish Faizan, Huma Zafar, Rabia Aqeel (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: It was a clinical audit conducted over 6 monthsperiod in order to determine the clinical characteristics of healthcare-associated infections (HAIs) in immunocompromised children with cancer in a developing country. Methods: It was a descriptive, cohort study conducted in the department of Pediatric Hematology/Oncology, University of Child Health Sciences, The Children’s Hospital Lahore. All patients age less than 16 years, admitted in the pediatric oncology unit, having neutropenia and any culture-proven HAI were included. Data was analyzed in SPSS 16.0. Results: The total number ofHAIs was 101 while the total number of infected patients was 83. The number of infections per 1000 patient days was 6.66. The most common HAI was bloodstream infection (BSI). Sixty-nine percent of HAIs were gram-negative while 31% were gram-positive. Klebsiella species was the most common gram-negative and Staphylococcal Aureus was the most common gram-positive organism. Pan-resistance was encountered in 25.74%, Carbepenam-resistant Enterobacteriaceae in 16%, Vancomycin-resistant Enterococci in 3%, and Methicillin-resistant Staphylococcus Aureus in 2%. Mean hospital stay was 20.22 days, 60.25% of patients were discharged, and 39.75% expired. Conclusion: Drug resistance is seen in about half of the HAIs. Gram-negative infections are the most common cause of HAIs in our setup.HAI and drug resistance areassociated with significant morbidity and mortality in immunocompromised children with cancer and a pose major challenge in their management especially in a resource-limited setting. Keywords: Childhood cancer, Drug resistance, Healthcare-associated infections, Low-middle-income country